Lithic technological strategies of Late Pleistocene hominins in the Daoshui River valley, Hunan province, central South China - Li, Yiyuan; Li, Hao; Sumner, Alexandra; Zhang, Jiafu (Frontiers in Earth Science, 2023)
The Late Pleistocene is a crucial period of dramatic changes in lithic technologies as well as interactions between modern humans and other archaic human groups. In this paper, we describe the technological analysis of lithic assemblages collected from 28 newly discovered Paleolithic sites along the Daoshui River, a tributary of the Lishui River (itself a tributary of Yangtze River) in northern Hunan Province, central South China. Luminescence dating of several sites in this region has provided a general Late Pleistocene age range for lithic assemblages. Technologically, high quality raw materials are predominantly exploited (e.g., chert and siliceous slate) and direct hard hammer percussion predominates which lacks core preparation though conceptually, some specimens do exhibit a certain degree of volumetric control and share other common features with prepared cores. Small flakes and flake tool production plays a primary role in the overall technological strategy, accompanying a small proportion of large flakes and Large Cutting Tools production. Our examination of lithic technologies in the region clearly contrasts with the traditional view of South China being characterized by a simple cobble tool industry over the course of the Pleistocene period. We further discuss the issue of the Middle Paleolithic in China, as well as the ecological adaptations of hominins in the Daoshui River valley within a Late Pleistocene climatic context.